Ankylosing Spondylitis: Patterns of Spinal Injury and Treatment Outcomes - Idiris Altun; Kasım Zafer Yuksel (Asian Spine Journal, 2016)
Study DesignRetrospective review.PurposeWe retrospectively reviewed our patients with ankylosing spondylitis (AS) to identify their patterns of spinal fractures to help clarify management strategies and the morbidity and mortality rates associated with this group of patients.Overview of LiteratureBecause of the brittleness of bone and long autofused spinal segments in AS, spinal fractures are common even after minor trauma and often associated with overt instability.MethodsBetween January 1, 1998 and March 2011, 30 patients (23 males, 7 females; mean age, 70.43 years; range, 45 to 95 years) with the radiographic diagnosis of AS of the spinal column had 42 fractures. Eight patients presented with significant trauma, 17 after falls, and 5 after minor falls or no recorded trauma. Eleven patients presented with a neurological injury, ranging from mild sensory loss to quadriplegia.ResultsThere were 16 compression and 10 transverse fractures, two Jefferson's fractures, one type II and two type III odontoid process fractures, and five fractures of the posterior spinal elements (including lamina and/or facet, three spinous process fractures, three transverse process fractures). Twenty-four fractures affected the craniocervical junction and/or cervical vertebrae, 17 were thoracic, and one involved the lumbar spine. The most affected vertebrae were C6 and T10. The mean follow-up was 29.9 months. One patient was lost to follow-up. Eighteen patients were treated conservatively with bed rest and bracing. Twelve patients underwent surgery for spinal stabilization either with an anterior, posterior or combined approach.ConclusionsNonsurgical treatment can be considered especially in the elderly patients with AS and spinal trauma but without instability or major neurological deficits. The nonfusion rate in conservatively treated patients is low. When treatment is selected for patients with spinal fractures and AS, the pattern of injury must be considered and the need for individualized treatment is paramount.